Functional Non-Coding RNA (microRNA / lncRNA) Profiling in Medicinal Chinese Herb Species and Their Link to Pharmacological Effects - Singh, Shubham; Malviya, Kapil; Batra, Navneet; Yaduwanshi, Phoolsingh; Shrivastava, Deepa; Singh Rajput, Dharmendra (Journal of Neonatal Surgery, 2025)
Traditional Chinese Medicine (TCM) comprises a diverse spectrum of medicinal herbs whose therapeutic efficacy arises from complex, multi-target molecular mechanisms that remain incompletely understood. While phytochemical constituents have been extensively investigated, the contribution of endogenous genomic regulators to herbal pharmacological effects has received comparatively less attention. In recent years, non-coding RNAs (ncRNAs), particularly microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), have emerged as critical modulators of gene expression in medicinal plants, influencing secondary metabolite biosynthesis, stress responses, and pharmacologically relevant pathways. This review critically synthesizes current evidence on the identification, expression profiling, and functional roles of plant-derived ncRNAs in key medicinal Chinese herbs, including Panax ginseng, Astragalus membranaceus, Glycyrrhiza uralensis, and Scutellaria baicalensis. By integrating transcriptomic findings, bioinformatics analyses, and experimentally validated pharmacological data, the review highlights how ncRNA-mediated regulatory networks shape the biosynthesis of bioactive compounds and contribute to therapeutic outcomes. Particular emphasis is placed on evaluating the strength of experimental evidence linking ncRNAs to pharmacological effects and on distinguishing validated mechanisms from purely predictive models. Unlike previous descriptive reviews, this work adopts a pharmacology-oriented perspective by critically assessing translational relevance, reproducibility challenges, and regulatory implications of ncRNA research in herbal medicine. The controversial hypothesis of cross-kingdom regulation by plant-derived ncRNAs is examined with balanced interpretation, outlining current limitations and methodological gaps. Collectively, this review provides a refined conceptual framework for ncRNA-guided herbal standardization, biomarker discovery, and precision-oriented phytotherapy, thereby advancing the molecular understanding and future application of Traditional Chinese Medicine.